Performance characteristics of crumb rubber modified asphalt mixed with reclaimed asphalt pavement and waste engine oil / Md Zahid Hossain Khan - Md Zahid , Hossain Khan (2022)
This study aimed to characterize the reclaimed asphalt pavement (RAP) mixes for the preparation of asphaltic concrete wearing course with 14 mm nominal maximum aggregate size (ACW14) mix. The RAP was incorporated with two waste materials comprising a 6% crumb rubber (CR) (by weight of virgin binder) as a binder modifier to enhance the rheological properties of the asphalt binder and 15% of waste engine oil (WEO) (by weight of aged binder) as a rejuvenator to restore the properties of the aged binder. A total of five different asphalt mixes were prepared where a replacement of 0%, 30%, 50%, 70%, and 100% RAP aggregates are incorporated in the mix (R0, R30, R50, R70, and R100). The Marshall method was used to determine the optimum binder content (OBC). Finally, the mechanical performances, resilient modulus (MR), indirect tensile fatigue, moisture susceptibility, and mass loss (ML) tests of the five ACW14 mixes were conducted and analysed. Based on the results, it was found that 15% WEO (by weight of aged binder) was able to soften the extracted aged binder. In addition, the OBC gradually decreased with the addition of RAP content. The R0 recorded the highest OBC value (5.9%), while the OBC values of R30, R50, R70, and R100 mixes were 5.8, 5.7, 5.5, and 5.5%, respectively. Furthermore, the results showed that the Marshall parameters, moisture susceptibility, and ML values of the RAP mixes complied with the criteria outlined by the Public Works Department Malaysia. According to the MR performance, the MR increased with the increment in RAP content, and R100 obtained the highest value. The moisture susceptibility test revealed that all RAP mixes were more resistant to moisture damage as the tensile strength ratio (TSR) values were higher than the standard value. In terms of fatigue resistance, the R30, R50, and R70 mixes showed better performance than the R0, while the R100 mix showed approximately 5% less resistance to fatigue than the R0. The ML test indicated that all RAP mixes exhibited highly ravelling resistance. Statistically, the amount of RAP and binder used significantly affected the ACW14 mix’s design performance.